The Effectiveness of Distance Learning In The Era of The Covid-19 Pandemic in Elementary Education / Efektivitas Pembelajaran Jarak Jauh di Era Pandemi Covid-19 di Pendidikan Dasar - Widiana Diana Mirianty; Palupi Lindiasari Samputra (STAI Ma'had Aly Al-Hikam Malang, 2021)
The Covid-19 pandemic that has hit the world has made the government impose restrictions on all community activities, including teaching and learning activities. To reduce the number of coronavirus transmissions in education, the government has implemented a distance learning policy. This study aims to determine the effectiveness of distance learning and what factors determine it. This study uses quantitative methods, this type of online survey research to respondents using the Google Forms application. The number of respondents was 119 parents of SDS Muhammadiyah 23 Jakarta’s students. The results found three factors that determined distance learning's effectiveness, namely the time factor in distance learning implementation, learning suitability level factor, and the quality factor of understanding information or subject. Distance Learning's performance at SDS Muhammadiyah 23 Jakarta was considered quite useful, with a percentage of 65.64% that supports the learning suitability level as the most dominant factor. However, some improvements are needed to create a pleasant learning atmosphere. Increasing face-to-face intensity by Zoom Meeting expects to increase student's understanding of the subject, build communication and bonding through the interaction between student, teacher, and other students, and make students more focused and motivated.